POLARISASI FLUORESENS PADA VIRGIN COCONUT OIL SETELAH MENGALAMI OZONASI - Azzahroh, Muffaricha; Sugito, Heri; Richardina, Very; Azam, Much.; Firdausi, Ketut Sofjan (BERKALA FISIKA, 2019)
This study investigates interaction effects between ozone and Virgin Coconut Oil (VCO) on fluorescence polarization. The ozonation time variations carried out on VCO were 30 minutes, 60 minutes and 90 minutes with ozone flow rates of 0.6L / minute. The degradation of VCO quality due to ozonation was determined by measuring changes in the fluorescence polarization angle of the light emitted by the sample, using a green laser pointer with a wavelength of 532 nm. Typical fluorescence polarization characteristics in the range of polarization angle variations from ïª = 0ï‚° to ïª = 180ï‚° are in accordance with the results of previous studies. Increasing the length of ozonation in the sample results in an increase in fluorescence polarization. The average fluorescence polarization in the range 0ï‚° ï‚£ ïª ï‚£ 180ï‚° rises linearly over the duration of ozonation, which indicates that ozone interactions are quite effective in degrading the quality of VCO. The validation results also obtained that the duration of ozonation also increases the amount of free fatty acids, however it needs to be further investigated whether the amount of free fatty acids directly contributes to fluorescence polarization. The study of interaction of ozone in solution in biophysics and also its benefits for skin therapy in medical science are very interesting to be further conducted.Keywords: Fluorescence polarization, Virgin Coconut Oil, polarization angle